Do Green Trust and Attitude Toward Green Products Have Effect on Green Purchase Behavior of Urban Society In Makassar? - Laela; Muhammad Asdar; Abdul Rahman Kadir; Dian Parawansa (PT Mattawang Mediatama Solution, 2022)
This study aims to analyze and investigate the involvement of variables in influencing green purchase behavior in Makassar City. The number of respondents sampled in this study was 90 people. The analysis method of this study is to use structural equation modeling. The results of the study analysis stated that the entire research hypothesis had a positive and significant effect. The findings of this study indicate that Consumers with a more substantial level of environmental awareness may think about their eco-social benefits when buying green products. A person who has a positive attitude towards environmental issues may be warier about the proportion of green ingredients and the effect of their trust in buying green products.